Korelasi Antara Keterampilan Proses Sains dan Keterampilan Berpikir Kritis Mahasiswa pada Matakuliah Bioteknologi Industri - Khusnul Khotimah; Utami Sri Hastuti; Ibrohim Ibrohim; Suhadi Suhadi (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This research was aimed to identify how great the relation between students’ science process skill and critical thinking skill in the Department of Agricultural Industry Technology, particularly on Industrial Biotechnology. This research was included into a correlational research. The population in this research was taken from about 50 fifth semester students of Agricultural Industry Technology Department, Faculty of Agriculture, Tribhuwana Tunggadewi University, Malang, who took subject of Industrial Biotechnology. The assessment was in form of multiple choice questions for science process skill and essay for critical thinking skill. The statistical analysis was linear regression method which was then continued through t-test and determinant coefficient test (R2). The research finding referred a correlation between science process skill and critical thinking skill. This finding was proved by tcount value 6,157 and p-value (0,000) < 0,05.